A polymer-perovskite quantum dot composite adhesive film and its preparation method and application
By modifying the perovskite quantum dots surface to form a thin layer of inorganic oxide and mixing it with polymers to prepare a composite adhesive film, the problem of poor stability of the existing adhesive film at high temperature is solved, and the thermal stability of the adhesive film and the efficiency of solar cells are significantly improved.
Patent Information
- Application Number
- CN202411991328.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing polymer-perovskite quantum dot composite film has poor stability under high temperature conditions, which can easily lead to the growth of perovskite quantum dot grains and lose their light conversion characteristics. At the same time, it is easy to hydrolyze and agglomerate under the action of water and light, affecting service life and battery efficiency.
The perovskite quantum dots are modified by surface modification agents, and the modifier forms a thin layer of inorganic oxide on the surface of the quantum dots through water and oxygen, enhancing its thermal stability. Then the modified perovskite quantum dot solution is mixed with the polymer solution, the solvent is removed and then extruded by melting to prepare a polymer-perovskite quantum dot composite adhesive film.
It significantly enhances the thermal stability of the adhesive film, prevents the grains of perovskite quantum dots from growing at high temperatures, maintains its light conversion ability, and improves the service life of the adhesive film and the photoelectric conversion efficiency of solar cells.
Smart Images

Figure CN119775918A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic adhesive films, and in particular to a polymer-perovskite quantum dot composite adhesive film and a preparation method and application thereof. Background Art
[0002] Photovoltaic film is a key material for encapsulation in photovoltaic modules. Although its cost is relatively low, about 6%, it has a crucial impact on the service life and power generation efficiency of photovoltaic modules. Photovoltaic film is used to bond cells, backplanes and photovoltaic glass. It provides structural support for fragile cells and can prevent cells from being corroded by the external environment, such as ultraviolet rays, oxygen, and moisture, thereby increasing the life of the cells. The film also has high light transmittance and anti-reflection effects, which can improve the efficiency of cells. In 2022, the domestic photovoltaic film industry's demand for polyethylene-vinyl acetate copolymer (EVA) accounted for 47% of the consumer market, and it is estimated that the global demand for photovoltaic film will reach 7 billion square meters in 2025.
[0003] Perovskite quantum dots are a type of zero-dimensional semiconductor material with an ABX3 perovskite structure. They have attracted much attention due to their good defect tolerance, high light absorption coefficient and conversion efficiency, and the ability to control the size of quantum dots by adjusting the ratio of halogen elements or synthesis conditions. Among them, the confinement engineering of perovskite quantum dots by polymers is very popular due to its simple process flow and low cost. Its main principle is that perovskite quantum dots are dispersed in polymer chains and organic ligands are modified on the surface of quantum dots. However, the existing polymer-quantum dot composite adhesive films have the following problems: Traditional cadmium-based quantum dots need to be prepared under high temperature conditions, which consumes a lot of energy. The temperature required for the EVA melting process is close to 90°C, and the perovskite quantum dots synthesized at low temperature are easily affected by high temperature and the grain size grows, thereby losing the light conversion characteristics. Since perovskite quantum dots are prone to anion exchange and have many surface defects, they are easily hydrolyzed under the action of polar molecules such as water, and are easily agglomerated and grains grow under light and high temperature. However, the micropores in the polymer cannot completely isolate the intrusion of air, so the stability in actual use is poor, and after a long time, the purpose of improving battery efficiency can no longer be achieved. Summary of the invention
[0004] The present invention provides a polymer-perovskite quantum dot composite adhesive film and a preparation method and application thereof. The perovskite quantum dots are modified by a surface modifier. Under the action of water and oxygen, the modifier adsorbed on the surface of the perovskite quantum dots is slowly hydrolyzed or oxidized to form an inorganic oxide thin layer. The perovskite quantum dot solution is mixed with a polymer solution, and the solvent is removed to obtain a composite masterbatch. The composite masterbatch is mixed with polymer particles and melt-extruded to obtain a polymer-perovskite quantum dot composite adhesive film. The thermal stability of the modified adhesive film of the present invention is significantly enhanced. The composite adhesive film is used to encapsulate crystalline silicon solar cells, which significantly improves the photoelectric conversion efficiency of the device.
[0005] The first object of the invention is to provide a method for preparing a polymer-perovskite quantum dot composite adhesive film, comprising the following steps:
[0006] The perovskite quantum dots are modified by a surface modifier, and after being acted upon by water and oxygen, the surface modifier is hydrolyzed or oxidized to obtain perovskite quantum dots protected by a thin layer of inorganic matter, thereby obtaining modified perovskite quantum dots; the surface modifier is a silane compound and / or a metal organic compound;
[0007] dissolving polymer particles in an organic solvent to obtain a polymer solution;
[0008] The modified perovskite quantum dots are mixed with a polymer solution, and heated and stirred for 30 minutes at 300-1000 rpm and 60-80° C.; the solvent is removed to obtain a polymer-perovskite quantum dot composite masterbatch, and the polymer-perovskite quantum dot composite masterbatch is mixed with polymer particles, and melt-extruded to obtain a polymer-perovskite quantum dot composite adhesive film.
[0009] As a preferred embodiment, based on the mass of the polymer-perovskite quantum dot composite film, the mass proportion of the surface modifier is 0.01% to 0.1%.
[0010] As a preferred embodiment, in the polymer-perovskite quantum dot composite film, the mass ratio of the modified perovskite quantum dots to the polymer is 1:10-100.
[0011] As a preferred embodiment, after adding the surface modifier with a concentration of 0.1 to 1 mol / L to the perovskite quantum dot solution, the solution is stirred for 30 min to 1 h in an air environment with a humidity of 30 to 50% to obtain modified perovskite quantum dots. If multiple modifiers are used, the first modifier is added, and after the above reaction conditions, another modifier is added, and the reaction environment conditions and time are the same as those of the first modifier.
[0012] As a preferred embodiment, the chemical formula of the perovskite quantum dot is ABX3, A4BX6, A2BX6, AB2X5, A2BX4, A3B2X9 or A n-1 B n+1 X 3n+1, n≥2; where A is CH3NH3 + 、NH2CHNH2 + 、C(NH2)3 + , Cs + , Li + 、Na + , K + , Rb + or one of the organic amine cations with carbon number ≥ 3, B is Pb 2+ , Cu 2+ Sn 2+ , Mn 2+ 、Zn 2+ 、Cd 2+ ,Ge 2+ , Sr 2 + 、Bi 3+ 、Eu 2+ , Yb 2+ , Sb 3+ 、Ti 3+ 、In 3+ , Cu + 、Ag + , Pd 2+ or Pd 4+ ; X is Cl - ,Br - , I - or SCN - .
[0013] As a preferred embodiment, the silane compound is 3-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, ureapropyltriethoxysilane or γ-aminopropylmethyldiethoxysilane; the metal organic compound is diethylzinc or trimethylaluminum.
[0014] As a preferred embodiment, the polymer is one or more of polyethylene vinyl acetate (EVA), ethylene-α-octene copolymer (POE), silicone resin, epoxy resin, polyvinyl butyral resin, polyethylene methyl methacrylate, and polymethyl methacrylate.
[0015] As a preferred embodiment, the method for preparing perovskite quantum dots comprises the following steps:
[0016] According to the chemical formula of the perovskite quantum dots, a site A precursor solution, a site B precursor solution and a site X precursor solution are prepared, the site A precursor solution is injected into the site B precursor solution and the site X precursor solution, reacted at 65-70° C. and 500 rpm for 1.5 h, and centrifuged to obtain a perovskite quantum dot solution.
[0017] The molar ratio of the A-site precursor to the B-site precursor is 1:10-5, and the molar ratio of the B-site precursor to the X-site precursor is 1:0.5-10.
[0018] The second object of the present invention is to provide a polymer-perovskite quantum dot composite adhesive film prepared by the above preparation method.
[0019] The third object of the present invention is to provide an application of the above polymer-perovskite quantum dot composite adhesive film in the preparation of solar cell photovoltaic adhesive film.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention first uses a surface modifier to modify the perovskite quantum dots. Under the action of water and oxygen, the modifier adsorbed on the surface of the perovskite quantum dots is slowly hydrolyzed or oxidized to generate an inorganic oxide thin layer, which is anchored on the surface of the perovskite quantum dots to form a modified shell. Due to the presence of the modified shell layer on the surface of the perovskite quantum dots, the fusion and growth of adjacent perovskite quantum dots are effectively inhibited, so the light conversion ability is retained. Then the perovskite quantum dot solution is mixed with a polymer solution, and the solvent is removed to obtain a composite masterbatch. The masterbatch is mixed with the polymer particles and melt-extruded to obtain a polymer-perovskite quantum dot composite adhesive film. The modified adhesive film has significantly enhanced thermal stability. The adhesive film is used to encapsulate crystalline silicon solar cells, which can significantly improve the photoelectric conversion efficiency of the device.
[0022] 3-aminopropyltriethoxysilane is used as a surface modifier. The amino group carried at one end of the molecule can be anchored on the surface of perovskite quantum dots, and because its binding energy with perovskite quantum dots is greater than oleic acid, octylamine and tetraheptyl ammonium bromide used in the synthesis process, it can partially replace these ligands. Under the action of moisture in the air, 3-aminopropyltriethoxysilane adsorbed on the surface of perovskite quantum dots is slowly hydrolyzed, and the three ethyl groups connected to the silicon oxygen bond become ethanol and fall off (other silane compounds, such as γ-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, ureapropyltriethoxysilane, γ-aminopropylmethyldiethoxysilane, have similar modification principles). At this time, the amino end of 3-aminopropyltriethoxysilane is still adsorbed on the quantum dots, while the section with Si-OC bond is converted into Si-OH and cross-linked with adjacent molecules to form O-Si-O bonds, that is, a thin shell is formed on the surface of the quantum dots. The metal organic compounds diethylzinc or trimethylaluminum are used as surface modifiers with strong binding ability to perovskite quantum dots. They can be adsorbed on the surface of quantum dots and can be in situ oxidized into a thin layer of corresponding metal oxide under the action of oxygen. They can also effectively inhibit the fusion and growth of adjacent perovskite quantum dots and retain the light conversion ability of perovskite quantum dots.
[0023] However, perovskite quantum dots that have not been surface-modified lose their light conversion ability due to Oswald ripening at high temperatures, which causes small grains to fuse into large grains. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Figure 1 is a comparative example 1 and Example 1, and their X-ray diffraction patterns after annealing at 90°C for 3 hours, wherein Figure a is the polymer-perovskite quantum dot composite film of comparative example 1, Figure b is the polymer-perovskite quantum dot composite film of Example 1, Figure c is the polymer-perovskite quantum dot composite film of comparative example 1 annealed at 90°C for 3 hours, and Figure d is the polymer-perovskite quantum dot composite film of Example 1 annealed at 90°C for 3 hours.
[0025] Figure 2 It is a scanning electron microscopy (SEM) image of the surface of the polymer-perovskite quantum dot composite film prepared in Example 1, wherein Figure a is the SEM image of the polymer-perovskite quantum dot composite film of Example 1, Figure b is the distribution map of the Cs element, Figure c is the distribution map of the Pb element, and Figure d is the distribution map of the Br element.
[0026] Figure 3This is a scanning electron microscopy (SEM) image of the surface of the polymer-perovskite quantum dot composite film prepared in Example 1 after annealing at 90°C for 3h, wherein Figure a is the SEM image of the polymer-perovskite quantum dot composite film of Example 1 after annealing at 90°C for 3h, Figure b is the distribution map of the Cs element in Figure a, Figure c is the distribution map of the Pb element in Figure a, and Figure d is the distribution map of the Br element in Figure a.
[0027] Figure 4 These are pictures of the composite adhesive films prepared in the comparative example and examples 1 to 7 under natural light and ultraviolet light, respectively.
[0028] Figure 5 It is the ultraviolet-visible spectrophotometer (UV-vis) graph of comparative example 1 and its annealing at 90° C. for 3 h.
[0029] Figure 6 It is the ultraviolet-visible spectrophotometer (UV-vis) graph of Example 1 and its 90° C. annealing for 3 hours.
[0030] Figure 7 This is the UV-visible spectrophotometer (UV-vis) graph of Example 2 and its 90°C annealing for 3h.
[0031] Figure 8 This is the UV-visible spectrophotometer (UV-vis) graph of Example 3 and its 90°C annealing for 3h.
[0032] Fig. 9 This is the UV-visible spectrophotometer (UV-vis) graph of Example 4 and its 90°C annealing for 3h.
[0033] Fig.10 This is the UV-visible spectrophotometer (UV-vis) graph of Example 5 and its 90°C annealing for 3h.
[0034] Fig.11 This is the UV-visible spectrophotometer (UV-vis) graph of Example 6 and its 90°C annealing for 3h.
[0035] Fig.12 This is the UV-visible spectrophotometer (UV-vis) graph of Example 7 and its 90°C annealing for 3h.
[0036] Fig.13 It is the steady-state fluorescence spectrum (PL) diagram of comparative example 1 and its film annealed at 90°C for 3h.
[0037] Fig.14 This is the steady-state fluorescence spectrum (PL) of Example 1 and the film annealed at 90°C for 3h.
[0038] Fig.15 This is the steady-state fluorescence spectrum (PL) of Example 2 and the film annealed at 90°C for 3h.
[0039] Fig.16 This is the steady-state fluorescence spectrum (PL) of Example 3 and the film annealed at 90°C for 3h.
[0040] Fig.17 This is the steady-state fluorescence spectrum (PL) of Example 4 and the film annealed at 90°C for 3h.
[0041] Fig.18 This is the steady-state fluorescence spectrum (PL) of Example 5 and the film annealed at 90°C for 3h.
[0042] Fig.19 This is the steady-state fluorescence spectrum (PL) of Example 6 and the film annealed at 90°C for 3h.
[0043] Fig. 20 This is the steady-state fluorescence spectrum (PL) of Example 7 and the film annealed at 90°C for 3h.
[0044] Fig.21 This is a comparison diagram of the current-voltage (JV) curves of the crystalline silicon battery encapsulated with the polymer-perovskite quantum dot composite adhesive film in Example 1 before and after annealing at 90°C.
[0045] Fig. 22 This is a comparison diagram of the current-voltage (JV) curves of the crystalline silicon battery encapsulated by the polymer-perovskite quantum dot composite adhesive film in Example 1 before and after annealing at 90°C.
[0046] Fig.23 This is a comparison diagram of the current-voltage (JV) curves of the crystalline silicon battery encapsulated by the polymer-perovskite quantum dot composite adhesive film in Example 2 before and after annealing at 90°C.
[0047] Fig.24 This is a comparison diagram of the current-voltage (JV) curves of the crystalline silicon battery encapsulated by the polymer-perovskite quantum dot composite adhesive film in Example 3 before and after annealing at 90°C.
[0048] Fig.25 This is a comparison diagram of the current-voltage (JV) curves of the crystalline silicon battery encapsulated by the polymer-perovskite quantum dot composite adhesive film of Example 4 before and after annealing at 90°C.
[0049] Fig.26 This is a comparison diagram of the current-voltage (JV) curves of the crystalline silicon battery encapsulated by the polymer-perovskite quantum dot composite adhesive film in Example 5 before and after annealing at 90°C.
[0050] Fig. 27 This is a comparison diagram of the current-voltage (JV) curves of the crystalline silicon battery encapsulated with the polymer-perovskite quantum dot composite adhesive film in Example 6 before and after annealing at 90°C.
[0051] Fig.28This is a comparison chart of the current-voltage (JV) curves of the crystalline silicon battery encapsulated by the polymer-perovskite quantum dot composite adhesive film in Example 7 before and after annealing at 90°C. DETAILED DESCRIPTION
[0052] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific examples, but the examples are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.
[0053] The background technology of the present invention mentioned that the existing polymer-quantum dot composite adhesive film has the following problems: First, the traditional cadmium quantum dots need to be prepared under high temperature conditions, which consumes a lot of energy. Second, the temperature required for the melting process of polyethylene-vinyl acetate (EVA) is close to 90°C, and the perovskite quantum dots synthesized at low temperature are affected by high temperature, which affects the growth of grain size, causing the perovskite quantum dots to lose their light conversion properties. Third, since perovskite quantum dots are prone to anion exchange and have many surface defects, they are easily hydrolyzed under the action of polar molecules such as water, and are easily agglomerated under light and high temperature, resulting in grain growth. The micropores in the polymer cannot completely isolate the intrusion of air, so the stability is poor in actual use, and the purpose of improving battery efficiency can no longer be achieved after a long time. To this end, the present invention provides a polymer-perovskite quantum dot composite adhesive film and its preparation method and application.
[0054] The technical effects of the present invention are described below in conjunction with specific embodiments and comparative examples.
[0055] Example 1
[0056] A method for preparing a polymer-perovskite quantum dot composite adhesive film comprises the following steps:
[0057] S1. Preparation of perovskite quantum dot solution
[0058] S11. Prepare cesium precursor solution (A-site precursor): add 0.0407 g Cs2CO3 and 2 mL oleic acid into 5 mL glass bottles respectively, and stir at 500 rpm and 70° C. to obtain a clear uniform solution.
[0059] S12. Prepare lead and bromine precursor solutions (B-site and X-site precursors): add 0.0588 g PbBr2 (B-site and X-site precursors), 0.1254 g tetraheptyl ammonium bromide (X-site precursor), 160 uL oleic acid, 160 uL octylamine and 16 mL 1,2,4-trimethylbenzene into a 20 mL glass bottle, and stir at 500 rpm and 70 ° C to obtain a clear uniform solution.
[0060] S13, forming a perovskite quantum dot solution: put 2 mL of lead precursor into a 5 mL glass bottle, stir at 500 rpm and 70° C., add 200 uL of cesium precursor, stir for 1.5 h, centrifuge at 2000 rpm for 5 min, take the supernatant, and obtain a perovskite quantum dot solution.
[0061] S2. Prepare EVA solution: add 1.6 g EVA particles and 16 mL 1,2,4-trimethylbenzene into a 20 mL glass bottle and stir at 500 rpm and 70 °C for a long enough time until a clear homogeneous solution is obtained;
[0062] S3. Modify the perovskite quantum dots: take 1 mL of the prepared perovskite quantum dot solution in a 5 mL glass bottle, add 10 μL of 3-aminopropyltriethoxysilane solution while stirring at 500 rpm and 70°C, and mix for 1 hour at 500 rpm, 70°C with the bottle mouth open in the air to obtain a perovskite quantum dot solution modified with 3-aminopropyltriethoxysilane.
[0063] S4. Prepare a 3-aminopropyltriethoxysilane-modified perovskite quantum dot-polymer mixed solution: mix the 3-aminopropyltriethoxysilane-modified perovskite quantum dot solution and the EVA solution in a volume ratio of 1:2, and heat and stir at 500 rpm and 70° C. for 30 minutes.
[0064] S5. Preparation of 3-aminopropyltriethoxysilane-modified perovskite quantum dot-polymer masterbatch: placing the 3-aminopropyltriethoxysilane-modified perovskite quantum dot-polymer mixed solution in a vacuum drying oven, drying at 60° C., and cutting to obtain a composite masterbatch with a particle size of 3 to 5 mm.
[0065] S6. Preparation of perovskite quantum dot-polymer composite film: the composite masterbatch and pure EVA particles are mixed at a mass ratio of 1:100, and a polymer-perovskite quantum dot composite film is obtained by extruding the mixture in a twin-screw extruder at 90° C. and 80 rpm.
[0066] Example 2
[0067] A method for preparing a polymer-perovskite quantum dot composite adhesive film comprises the following steps:
[0068] S1. Prepare a perovskite quantum dot solution, as in Example 1.
[0069] S2. Prepare EVA solution: same as in Example 1.
[0070] S3. Modify the perovskite quantum dots: take 1 mL of the prepared perovskite quantum dot solution in a 5 mL glass bottle, add 10 μL of γ-aminopropyltrimethoxysilane solution while stirring at 500 rpm and 70°C, and mix for 1 hour at 500 rpm, 70°C with the bottle mouth open in the air to obtain a perovskite quantum dot solution modified with γ-aminopropyltrimethoxysilane.
[0071] S4. Prepare a γ-aminopropyltrimethoxysilane-modified perovskite quantum dot-polymer mixed solution: mix the γ-aminopropyltrimethoxysilane-modified perovskite quantum dot solution and the EVA solution in a volume ratio of 1:2, and heat and stir at 500 rpm and 70° C. for 30 minutes.
[0072] S5. Preparation of γ-aminopropyltrimethoxysilane-modified perovskite quantum dot-polymer masterbatch: placing the γ-aminopropyltrimethoxysilane-modified perovskite quantum dot-polymer mixed solution in a vacuum drying oven, drying at 60° C., and cutting to obtain a composite masterbatch with a particle size of 3 to 5 mm.
[0073] S6. Preparation of perovskite quantum dot-polymer composite film: the composite masterbatch and pure EVA particles are mixed at a mass ratio of 1:100, and a polymer-perovskite quantum dot composite film is obtained by extruding the mixture in a twin-screw extruder at 90° C. and 80 rpm.
[0074] Example 3
[0075] A method for preparing a polymer-perovskite quantum dot composite adhesive film comprises the following steps:
[0076] S1. Prepare a perovskite quantum dot solution, as in Example 1.
[0077] S2. Prepare EVA solution: same as in Example 1.
[0078] S3. Modify the perovskite quantum dots: take 1 mL of the prepared perovskite quantum dot solution in a 5 mL glass bottle, add 10 μL of γ-glycidyloxypropyltrimethoxysilane solution while stirring at 500 rpm and 70°C, and mix for 1 hour at 500 rpm, 70°C with the bottle mouth open in the air to obtain a perovskite quantum dot solution modified with γ-glycidyloxypropyltrimethoxysilane.
[0079] S4. Prepare a γ-glycidyloxypropyltrimethoxysilane-modified perovskite quantum dot-polymer mixed solution: mix the γ-glycidyloxypropyltrimethoxysilane-modified perovskite quantum dot solution and the EVA solution in a volume ratio of 1:2, and heat and stir at 500 rpm and 70°C for 30 minutes.
[0080] S5. Preparation of γ-glycidyloxypropyltrimethoxysilane-modified perovskite quantum dot-polymer masterbatch: placing the γ-glycidyloxypropyltrimethoxysilane-modified perovskite quantum dot-polymer mixture in a vacuum drying oven, drying at 60° C., and cutting to obtain a composite masterbatch with a particle size of 3-5 mm.
[0081] S6. Preparation of perovskite quantum dot-polymer composite film: the composite masterbatch and pure EVA particles are mixed at a mass ratio of 1:100, and a polymer-perovskite quantum dot composite film is obtained by extruding the mixture in a twin-screw extruder at 90° C. and 80 rpm.
[0082] Example 4
[0083] A method for preparing a polymer-perovskite quantum dot composite adhesive film comprises the following steps:
[0084] S1. Prepare a perovskite quantum dot solution, as in Example 1.
[0085] S2. Prepare EVA solution: same as in Example 1.
[0086] S3. Modify the perovskite quantum dots: take 1 mL of the prepared perovskite quantum dot solution in a 5 mL glass bottle, add 10 μL of γ-aminopropylmethyldiethoxysilane solution while stirring at 500 rpm and 70°C, and mix for 1 hour at 500 rpm, 70°C with the bottle mouth open in the air to obtain a perovskite quantum dot solution modified with γ-aminopropylmethyldiethoxysilane.
[0087] S4. Prepare a γ-aminopropylmethyldiethoxysilane-modified perovskite quantum dot-polymer mixed solution: mix the γ-aminopropylmethyldiethoxysilane-modified perovskite quantum dot solution and the EVA solution in a volume ratio of 1:2, and heat and stir at 500 rpm and 70°C for 30 minutes.
[0088] S5. Preparation of γ-aminopropylmethyldiethoxysilane-modified perovskite quantum dot-polymer masterbatch: placing the γ-aminopropylmethyldiethoxysilane-modified perovskite quantum dot-polymer mixed solution in a vacuum drying oven, drying at 60° C., and cutting to obtain a composite masterbatch with a particle size of 3-5 mm.
[0089] S6. Preparation of perovskite quantum dot-polymer composite film: the composite masterbatch and pure EVA particles are mixed at a mass ratio of 1:100, and a polymer-perovskite quantum dot composite film is obtained by extruding the mixture in a twin-screw extruder at 90° C. and 80 rpm.
[0090] Example 5
[0091] A method for preparing a polymer-perovskite quantum dot composite adhesive film comprises the following steps:
[0092] S1. Prepare a perovskite quantum dot solution, as in Example 1.
[0093] S2. Prepare EVA solution: same as in Example 1.
[0094] S3. Modify the perovskite quantum dots: take 1 mL of the prepared perovskite quantum dot solution in a 5 mL glass bottle, add 10 μL of ureapropyltriethoxysilane solution while stirring at 500 rpm and 70°C, and mix for 1 hour at 500 rpm, 70°C with the bottle mouth open in the air to obtain a perovskite quantum dot solution modified with ureapropyltriethoxysilane.
[0095] S4. Preparation of ureapropyltriethoxysilane-modified perovskite quantum dot-polymer mixed solution: The ureapropyltriethoxysilane-modified perovskite quantum dot solution and the EVA solution were mixed in a volume ratio of 1:2, and heated and stirred at 500 rpm and 70° C. for 30 min.
[0096] S5. Preparation of ureapropyltriethoxysilane-modified perovskite quantum dot-polymer masterbatch: placing the ureapropyltriethoxysilane-modified perovskite quantum dot-polymer mixed solution in a vacuum drying oven, drying at 60° C., and cutting to obtain a composite masterbatch with a particle size of 3-5 mm.
[0097] S6. Preparation of perovskite quantum dot-polymer composite film: the composite masterbatch and pure EVA particles are mixed at a mass ratio of 1:100, and a polymer-perovskite quantum dot composite film is obtained by extruding the mixture in a twin-screw extruder at 90° C. and 80 rpm.
[0098] Example 6
[0099] Example 6 shows an adhesive film made by mixing quantum dots modified with 3-aminopropyltriethoxysilane and trimethylaluminum in sequence with EVA.
[0100] A method for preparing a polymer-perovskite quantum dot composite adhesive film comprises the following steps:
[0101] S1. Prepare a perovskite quantum dot solution, as in Example 1.
[0102] S2. Prepare EVA solution: same as in Example 1.
[0103] S3. Modification of perovskite quantum dots: 1 mL of the prepared perovskite quantum dot solution was placed in a 5 mL glass bottle, and 10 μL of 3-aminopropyltriethoxysilane solution was added while stirring at 500 rpm and 70°C, and mixed for 1 h at 500 rpm, 70°C, with the bottle mouth open in the air, to obtain a perovskite quantum dot solution modified with 3-aminopropyltriethoxysilane. Subsequently, 10 μL of trimethylaluminum solution (0.1 mol / L) was added, and mixed for 1 h at 500 rpm, 70°C, with the bottle mouth open in the air.
[0104] S4. Prepare a perovskite quantum dot-polymer mixed solution modified sequentially with 3-aminopropyltriethoxysilane and trimethylaluminum: mix the perovskite quantum dot solution modified sequentially with 3-aminopropyltriethoxysilane and trimethylaluminum with the EVA solution in a volume ratio of 1:2, and heat and stir at 500 rpm and 70°C for 30 min.
[0105] S5. Preparation of perovskite quantum dot-polymer masterbatch modified with 3-aminopropyltriethoxysilane and trimethylaluminum in sequence: placing the perovskite quantum dot-polymer mixture modified with 3-aminopropyltriethoxysilane and trimethylaluminum in sequence in a vacuum drying oven, drying at 60° C. and cutting to obtain composite masterbatch with a particle size of 3 to 5 mm.
[0106] S6. Preparation of perovskite quantum dot-polymer composite film: the composite masterbatch and pure EVA particles are mixed at a mass ratio of 1:100, and a polymer-perovskite quantum dot composite film is obtained by extruding the mixture in a twin-screw extruder at 90° C. and 80 rpm.
[0107] Example 7
[0108] Example 7 shows that the film prepared by mixing 3-aminopropyltriethoxysilane-modified quantum dots with POE includes the following steps:
[0109] S1. Prepare a perovskite quantum dot solution, as in Example 1.
[0110] S2. Prepare POE solution: Add 1.6 g POE particles and 16 mL 1,2,4-trimethylbenzene into a 20 mL glass bottle and stir at 500 rpm and 70° C. for a sufficient time until a clear uniform solution is obtained.
[0111] S3. Modify the perovskite quantum dots: take 1 mL of the prepared perovskite quantum dot solution in a 5 mL glass bottle, add 10 μL of 3-aminopropyltriethoxysilane solution while stirring at 500 rpm and 70°C, and mix for 1 hour at 500 rpm, 70°C with the bottle mouth open in the air to obtain a perovskite quantum dot solution modified with 3-aminopropyltriethoxysilane.
[0112] S4. Prepare a 3-aminopropyltriethoxysilane-modified perovskite quantum dot-polymer mixed solution: mix the 3-aminopropyltriethoxysilane-modified perovskite quantum dot solution and the EVA solution in a volume ratio of 1:2, and heat and stir at 500 rpm and 70° C. for 30 minutes.
[0113] S5. Preparation of 3-aminopropyltriethoxysilane-modified perovskite quantum dot-polymer masterbatch: placing the 3-aminopropyltriethoxysilane-modified perovskite quantum dot-polymer mixture in a vacuum drying oven, drying at 60° C., and cutting to obtain a composite masterbatch with a particle size of 3-5 mm.
[0114] S6. Preparation of perovskite quantum dot-polymer composite film: the composite masterbatch and pure EVA particles are mixed at a mass ratio of 1:100, and a polymer-perovskite quantum dot composite film is obtained by extruding the mixture in a twin-screw extruder at 90° C. and 80 rpm.
[0115] In order to further illustrate the technical effect of the present invention, the present invention also sets a comparative example, which is as follows:
[0116] Comparative Example 1
[0117] Compared with Example 1, the difference is that no surface modifier is used to modify the perovskite quantum dots, and the following steps are included:
[0118] S1. Prepare a perovskite quantum dot solution, as in Example 1.
[0119] S2. Prepare EVA solution, same as in Example 1.
[0120] S3, preparing a perovskite quantum dot-polymer mixed solution: mixing the perovskite quantum dot solution and the EVA solution in a volume ratio of 1:2, and heating and stirring at 500 rpm and 70° C. for 30 min;
[0121] S4. Preparation of perovskite quantum dot-polymer masterbatch: placing the perovskite quantum dot-polymer mixed solution in a vacuum drying oven, drying at 60° C., and cutting to obtain a composite masterbatch with a particle size of 3-5 mm.
[0122] S5. Preparation of perovskite quantum dot-polymer composite film: The composite masterbatch and pure EVA particles are mixed at a mass ratio of 1:100, and a polymer-perovskite quantum dot composite film is obtained by extruding the mixture in a twin-screw extruder at 90° C. and 80 rpm.
[0123] A series of tests were performed on the composite adhesive films prepared in Examples 1 to 7 of the present invention and Comparative Example 1.
[0124] 1. Crystalline silicon cell packaging and testing
[0125] The efficiency of crystalline silicon solar cell wafers is tested under standard lighting conditions.
[0126] The backplane, pure EVA or POE film, crystalline silicon cell, perovskite quantum dot-polymer composite film and photovoltaic glass are stacked in sequence and hot-pressed and packaged using a laminator.
[0127] Under standard test conditions, the JV performance curve of the packaged crystalline silicon battery is tested to compare the performance of the original battery and the packaged battery.
[0128] 2. Thermal stability test
[0129] The perovskite quantum dot-polymer composite film and the encapsulated battery obtained above were placed on a hot plate at 90° C. for annealing for 3 h, and the above test was repeated on the obtained samples.
[0130] The main results are as follows:
[0131] like Figure 1 Shown is the XRD pattern of perovskite quantum dots. Figure 1 The peaks of the spectrum lines 15.1° and 30.4° in (a) and (b) correspond to the (001) and (002) crystal planes of the perovskite quantum dots CsPbBr3, respectively, indicating that both pure quantum dots and quantum dots modified with 3-aminopropyltriethoxysilane belong to the CsPbBr3 structure. After annealing at 90°C, the crystal structures of both have not changed, but the half-peak width of the diffraction peak of the unmodified quantum dots has decreased, which is consistent with the fact that the quantum dots grow at high temperatures. However, there is no obvious change in the quantum dots modified with 3-aminopropyltriethoxysilane. This proves the beneficial effect of the introduction of 3-aminopropyltriethoxysilane on improving the thermal stability of quantum dots.
[0132] like Figure 2 As shown in the SEM image of the perovskite quantum dot-EVA composite film modified with 3-aminopropyltriethoxysilane, Figure (a) shows that the composite film has a smooth surface morphology. From the element mapping results Figures (b), (c), and (d), it can be seen that the three elements Cs, Pb, and Br are evenly distributed in the composite film. After annealing at 90°C for 3 hours, the composite film Figure 3 As shown in the figure, the surface of the composite film is still relatively smooth. The element mapping results show that the three elements Cs, Pb, and Br are still evenly distributed. This shows that 3-aminopropyltriethoxysilane modification has a beneficial effect on the thermal stability of quantum dots.
[0133] like Figure 4 As shown, the pictures of the quantum dot-polymer composite films prepared in Comparative Example 1 and Examples 1-7 under natural light and ultraviolet light show that the luminescence ability of the films is improved after surface modification treatment.
[0134] like Figure 5 to Figure 12 As shown, the UV-visible transmission spectrum images of the composite adhesive films prepared in Comparative Example 1 and Examples 1-7. As can be seen from the figure, the modified composite adhesive film has a higher transmittance in the range of 400-800nm than the unmodified composite adhesive film, indicating that after the modification, the dispersion of quantum dots in the polymer is enhanced, effectively reducing light loss. After annealing at 90°C for 3 hours, the unmodified quantum dot adhesive film has a reduced absorption capacity for short-wavelength photons in the range of 200-400nm due to the agglomeration and growth of quantum dots, and the light conversion capacity of the adhesive film is reduced.
[0135] like Figures 13 to 20 As shown, the fluorescence spectrum images of the composite adhesive films prepared in Comparative Example 1 and Examples 1 to 7. After annealing at 90°C for 3 hours, the fluorescence peak intensity of the unmodified quantum dot adhesive film dropped significantly, only about 3% of the initial intensity. However, the modified quantum dot adhesive film can maintain good fluorescence performance. This shows that the heat resistance stability of the modified quantum dot adhesive film is significantly improved.
[0136] like Figure 21 to Figure 28 As shown, based on the JV curves of the cells before and after the composite film encapsulation of Comparative Example 1 and Examples 1 to 7 and after annealing at 90°C for 3 hours, the photovoltaic performance parameters of the device are obtained, as shown in Table 1. From the test results, it can be seen that for Comparative Example 1, before annealing at 90°C, the efficiency is increased by 0.37% compared with the unencapsulated cell, but the efficiency of the device after 90°C treatment is significantly attenuated, decreasing by 0.49%. This is because under high temperature treatment, the quantum dots in the film agglomerate and the light conversion ability decreases; for Examples 1 to 7, the thermal stability of the modified quantum dot material is enhanced, and after 90°C treatment, a certain efficiency improvement can still be maintained.
[0137] Table 1 Photovoltaic performance parameters of battery devices
[0138]
[0139]
[0140] In summary, the polymer-perovskite quantum dot composite adhesive film provided by the present invention can convert high-energy ultraviolet light that cannot be absorbed by solar cells into light that can be used by solar cells. After the encapsulated battery device is subjected to high-temperature treatment, it can still maintain a certain efficiency improvement capability.
[0141] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a polymer-perovskite quantum dot composite film, characterized in that: The following steps are involved: The perovskite quantum dots are modified by a surface modifier, and after being acted upon by water and oxygen, the surface modifier is hydrolyzed or oxidized to obtain perovskite quantum dots protected by a thin layer of inorganic matter, thereby obtaining modified perovskite quantum dots; the surface modifier is a silane compound and / or a metal organic compound; dissolving polymer particles in an organic solvent to obtain a polymer solution; The modified perovskite quantum dots are mixed with a polymer solution, and the solvent is removed to obtain a polymer-perovskite quantum dot composite masterbatch. The polymer-perovskite quantum dot composite masterbatch is mixed with polymer particles, and melt-extruded to obtain a polymer-perovskite quantum dot composite adhesive film.
2. The preparation method according to claim 1, characterized in that: Based on the mass of the polymer-perovskite quantum dot composite adhesive film, the mass proportion of the surface modifier is 0.01% to 0.1%.
3. The preparation method according to claim 1, characterized in that: In the polymer-perovskite quantum dot composite adhesive film, the mass ratio of the modified perovskite quantum dots to the polymer is 1:10-100.
4. The preparation method according to claim 1, characterized in that: After adding the surface modifier with a concentration of 0.1-1 mol / L into the perovskite quantum dot solution, the solution is stirred for 30 minutes to 1 hour in an air environment with a humidity of 30-50%, so as to obtain modified perovskite quantum dots.
5. The preparation method according to claim 1, characterized in that: The chemical formula of the perovskite quantum dot is ABX3, A4BX6, A2BX6, AB2X5, A2BX4, A3B2X9 or A n-1 B n+1 X 3n+1, n≥2; Where A is CH3NH3 + NH2CHNH2 + 、C(NH2)3 + , Cs + , Li + 、Na + , K + , Rb + or one of the organic amine cations with carbon number ≥ 3, B is Pb 2+ , Cu 2+ Sn 2+ , Mn 2+ 、Zn 2+ 、Cd 2+ ,Ge 2+ , Sr 2+ 、Bi 3+ 、Eu 2+ , Yb 2+ , Sb 3+ 、Ti 3+ 、In 3+ , Cu + 、Ag + , Pd 2+ or Pd 4+ ; X is Cl - ,Br - , I - or SCN - .
6. The preparation method according to claim 1, characterized in that: The silane compound is 3-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, γ-glycidyloxypropyl trimethoxysilane, ureapropyl triethoxysilane or γ-aminopropyl methyl diethoxysilane; the metal organic compound is diethyl zinc or trimethyl aluminum.
7. The preparation method according to claim 1, characterized in that: The polymer is one or more of polyethylene-vinyl acetate, ethylene-α-octene copolymer, silicone resin, epoxy resin, polyvinyl butyral resin, polyethylene-methyl methacrylate, and polymethyl methacrylate.
8. The preparation method according to claim 5, characterized in that: The method for preparing perovskite quantum dots comprises the following steps: According to the chemical formula of the perovskite quantum dot, a site A precursor solution, a site B precursor solution and a site X precursor solution are prepared, the site A precursor solution is injected into the site B precursor solution and the site X precursor solution, reacted at 65-70° C., and centrifuged to obtain a perovskite quantum dot solution; The molar ratio of the A-site precursor to the B-site precursor is 1:10-5, and the molar ratio of the B-site precursor to the X-site precursor is 1:0.5-10.
9. A polymer-perovskite quantum dot composite adhesive film prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the polymer-perovskite quantum dot composite adhesive film according to claim 9 in preparing a photovoltaic adhesive film for solar cells.
Citation Information
Cited By
Quantum dot light conversion packaging adhesive film and preparation method and application thereof
CN119979054A